AI and IoT Meet Mobile Machines Towards a Smart Working Site - Xiang, Yusheng (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
Infrastructure construction is society's cornerstone and economics' catalyst. Therefore, improving mobile machinery's efficiency and reducing their cost of use have enormous economic benefits in the vast and growing construction market. In this thesis, I envision a novel concept smart working site to increase productivity through fleet management from multiple aspects and with Artificial Intelligence (AI) and Internet of Things (IoT).